VD_FINDINFO Décision / 2015 / 711 vom 13. August 2015 - VD Tribunal cantonal (2015)
CONTRAVENTION, JUGE UNIQUE, CALCUL DU DÉLAI | 398 al. 4 CPP (CH), 399 al. 3 CPP (CH), 403 al. 1 let. a CPP (CH), 403 al. 2 CPP (CH), 90 CPP (CH), 14 al. 3 LVCPP